Da'wah for Breast Cancer Patients: A Case Study at Kolej Universiti Islam Malaysia - Husna Bt Mohd Baki (Universiti Sains Islam Malaysia, 2011)
Nowadays, Da'wah Islamiyyah is an important aspect in society living. This academic project is based on third year female students from the Faculty of Da'wah and Islamic Management, KUIM. The study aims to gather student's views on understanding and comprehending the importance and needs of performing Da'wah for Breast Cancer Patients. Library study, questionnaires and reviewing relevant documents are the tools employed for data gathering purposes. The finding indicates that students believe Da'wah for Breast Cancer Patients is important and needs to be performed amongst them.